Why There Are No Normative Reasons for Belief - Schmidt, Sebastian (FINO Graduate Conference on Contemporary Issues Across Ethics and Epistemology, 2018)
I argue that reasons for belief are no normative reasons because it is sometimes true that we ought to cause ourselves not to respond correctly to our reasons for belie
Keywords: belief; normativity; rationality; reasons